2007
DOI: 10.1007/s11103-007-9255-7
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide survey of HD-Zip genes in rice and analysis of drought-responsive family members

Abstract: The homeodomain leucine zipper (HD-Zip) genes encode transcription factors that have diverse functions in plant development and have often been implicated in stress adaptation. The HD-Zip genes are the most abundant group of homeobox (HB) genes in plants and do not occur in other eukaryotes. This paper describes the complete annotation of the HD-Zip families I, II and III from rice and compares these gene families with Arabidopsis in a phylogeny reconstruction. Orthologous pairs of rice and Arabidopsis HD-Zip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
215
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(230 citation statements)
references
References 87 publications
(95 reference statements)
12
215
1
2
Order By: Relevance
“…The MEME result revealed that HD-ZIP III proteins have a C-terminal extension of about 150 amino acids termed MEKHLA. This region was also well conserved in the HD-ZIP III proteins from both monocots (O. sativa) and dicots (Arabidopsis) (Prigge et al, 2005;Agalou et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The MEME result revealed that HD-ZIP III proteins have a C-terminal extension of about 150 amino acids termed MEKHLA. This region was also well conserved in the HD-ZIP III proteins from both monocots (O. sativa) and dicots (Arabidopsis) (Prigge et al, 2005;Agalou et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…The availability of the complete genome sequences of peach and the previous identification of HD-ZIP family genes from some plant species (Aso et al, 1999;Agalou et al, 2008;Övernäs, 2010;Hu et al, 2012) enabled a comparison of individual families and groups of these genes with those in Arabidopsis (Henriksson et al, 2005;Prigge et al, 2005;Nakamura et al, 2006;Ciarbelli et al, 2008). Although peach has a large genome of 220-230 Mbp (Jung et al, 2008), which is larger than that of A. thaliana (145 Mbp) (Huala et al, 2001) and smaller than that of O. sativa (430 Mbp) (Goff et al, 2002), the number of genes in the HD-ZIP family in peach (33) is not more than that in A. thaliana (47) and is not much less than that in O. sativa (38).…”
Section: Discussionmentioning
confidence: 99%
“…The original β clade was also divided into β1 and β2 clades as reported in maize and rice. 42,43) β2, φ1, ε clades were grouped by tomato and Arabidopsis genes. SlHZ12 in β1 clade, SlHZ08, -13 and -28,-01 in α clade, SlHZ16, -17, -18, -19 in δ clade, SlHZ20, -32, -41, -05 in γ clade were clustered with Arabidopsis and rice in their clades.…”
Section: Phylogenetic Classification and Structural Analysis Of Slhz mentioning
confidence: 99%
“…41) However, in this study, ATHB54 did not had any counterparts of two other species or did not belong to any clade as Agalou reported. 42) ATHB54 is a atypical HD-Zip I protein with an extremely long CTR (325aa) which a RNA recognition motif can be identified in. 10) In class II, HD-Zip genes of three species were divided into several subclasses as reported in Arabidopsis.…”
Section: Phylogenetic Classification and Structural Analysis Of Slhz mentioning
confidence: 99%
“…Many members of MYB, AP2/ERF, bZIP, and HD-ZIP families not only play important roles in the regulation of plant tolerance to abiotic stresses, but also function as regulators of responses to biotic stress, particularly with respect to activation of anti-pathogen defenses [30][31][32][33][34][35][36][37][38][39]. In rice, transgenic technology approaches indicated that at least five bZIP genes, nine AP2/ERF genes, and one MYB genes regulated tolerance to drought [40].…”
Section: Stress-responsive Tfs Possibly Regulate Tolerance In Ramiementioning
confidence: 99%